More than just having the right headings: Supporting students' report writing - Michelle Reid (Association for Learning Development in Higher Education (ALDinHE), 2010)
We tend to assume that report writing is more straightforward than essay writing and that it varies greatly between academic disciplines in HE. However, there is relatively little research on reports as an academic genre of writing. Consequently, the University of Reading, as part of the LearnHigher CETL, conducted a series of qualitative interviews with subject academics from a range of departments in order to investigate their needs when supporting student report writing. This research shows that report writing varies not only between subjects but often within modules in the same subject, and it also encompasses a far wider range of informative writing. These findings highlight the need to consider the audience and purpose of each report, to emphasise the reasons behind the formal structure of reports, and to show reports as a means of formalising and communicating a research process, rather than only a series of structural characteristics. This research has also informed the creation of adaptable report writing resources freely available on the LearnHigher website.